2020
DOI: 10.3390/cancers12071717
|View full text |Cite
|
Sign up to set email alerts
|

The Intermediate Filament Synemin Regulates Non-Homologous End Joining in an ATM-Dependent Manner

Abstract: The treatment resistance of cancer cells is a multifaceted process in which DNA repair emerged as a potential therapeutic target. DNA repair is predominantly conducted by nuclear events; yet, how extra-nuclear cues impact the DNA damage response is largely unknown. Here, using a high-throughput RNAi-based screen in three-dimensionally-grown cell cultures of head and neck squamous cell carcinoma (HNSCC), we identified novel focal adhesion proteins controlling DNA repair, including the intermediate filam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…Intriguingly, these findings about synemin/c-Abl interactions are also consistent with a previous report demonstrating interactions of synemin and DNA-PK to co-control DSB repair [ 23 ]. Several publications document a complex signaling network between c-Abl and different DNA repair proteins.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Intriguingly, these findings about synemin/c-Abl interactions are also consistent with a previous report demonstrating interactions of synemin and DNA-PK to co-control DSB repair [ 23 ]. Several publications document a complex signaling network between c-Abl and different DNA repair proteins.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, we reported that the intermediate filament synemin is involved in the response to X-ray irradiation in dependence on DNA-PKcs [ 23 ]. To further unravel the complex involvement of synemin in the regulation of radiation survival, we performed synemin knockdowns using three different siRNAs and one esiRNA (endoribonuclease-prepared siRNA) in two 3D lrECM grown HNSCC cell lines, i.e., Cal33 and SAS ( Figure 1 A–F and Figure S1A,B ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations